Characterisation of the Selective Reduced Uteroplacental Perfusion (sRUPP) Model of Preeclampsia - Morton, J. S. (Sci Rep, 2019)
Preeclampsia is a complication of pregnancy characterised by gestational hypertension, proteinuria and/or end organ disease. The reduced uteroplacental perfusion (RUPP) model, via partial occlusion of the lower abdominal aorta, mimics insufficient placental perfusion as a primary causal characteristic of preeclampsia. However, a major limitation of the RUPP model is that perfusion is reduced to the entire hindquarters of the rat resulting in hindlimb ischemia. We hypothesised that clipping the uterine and ovarian arteries in the selective (s)RUPP model would provoke signs of preeclampsia while avoiding systemic ischemia. Sham, RUPP or sRUPP procedures were performed in pregnant Sprague Dawley rats on gestational day (GD)14. On GD21 uterine blood flow was significantly reduced in both the RUPP and sRUPP models while aortic flow was reduced only in RUPP. Both models resulted in increased MAP, increased vascular oxidative stress (superoxide generation), increased pro-inflammatory (RANTES) and reduced pro-angiogenic (endoglin) mediators. Vascular compliance and constriction were unaltered in either RUPP or sRUPP groups. In summary, refinements to the RUPP model simultaneously maintain the characteristic phenotype of preeclampsia and avoid peripheral ischemia; providing a useful tool which may be used to increase our knowledge and bring us closer to a solution for women affected by preeclampsia.